La fortuna dei classici - Pardi, Francesco (Ri-Vista. Research for landscape architecture, 2015)
In the ten years of working at his book, Sereni went through Italy, seeing landscapes with a warping, a character and a diversity strongly linked to local and regional places, so far from the current spread grid, with a big dilatation of lots done by the functional needs of the modern mechanized crops. The strength of the historical stratification of an half of a century ago landscape, what that classics could see, is gone now, reduced to an iconographic find and detectable in the contemporary scenes only in the form of a rare and residual exceptions. Overviewing the current rural landscape would suggest the young author to write an history of rural landscape?